Comment on “Parabolic Changes in Pain Scores Among Partial Herpes Zoster Patients: A Retrospective Study” [Letter] - Tan Y; Kang Y; Li R (Journal of Pain Research)
Yingjian Tan,1,* Yue Kang,2,* Rui Li1 1Department of Dermatology, Fuzhou First General Hospital, Fuzhou, People’s Republic of China; 2Department of Respiratory and Critical Care, Xinxiang Central Hospital, Xinxiang, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yingjian Tan; Rui Li, Email dr.yingjian.tan@gmail.com; 292430384@qq.com